Neurogenic skin inflammation – an updated knowledge - Teresiak, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Neuropeptides are biologically active peptides, present in neurons of central and peripheral nervous system and involved in the transmission of signals between nerve cells and immune cells. They act as neuromodulators, neurotransmitters, neurotrophins and neurohormons. Neuropeptides are produced mostly in afferent, unmyelinated C fibres or myelinated A delta fibres, in response to nociceptive stimulation as well as in fibres of autonomic nervous system. Receptors for neuropeptides are expressed on the surface of several immune cells. Opioid, nonopioid neuropeptides and neurotrophins are produced by dermal and immune cells. Exchange of information between the nervous and the immune system is conducted by the endocrine or paracrine release of neuropeptides. Local immunological reaction is regulated by neuropeptides. They affect actvity of lymphocytes T, antigen presenting cells, adhesion molecules as well as proliferation of immune cells, synthesis of proinflammatory cytokines and immunoglobulins. Set of events reffered to as ”neurogenic inflammation” is regulated by neuropeptides. Within the skin, A delta fibres are responsible for vasodilatation and C fibres for plasma leakage. Some neuropeptides are potent releasers of histamine from mast cells and they may also stimulate proliferation of keratinocytes, fibroblasts and endothelial cells.